The Toxicity Effects of Ash Emitted from Durah Power Plant on Pleuroxus hamulatus Birge, 1910 (Cladocera: Crustacea) - Al-Naymi, Noor A. Sh.; Nashaat, Muhanned R.; Abed, Intisar F. (Iraqi Journal of Science, 2024)
Durah power plant (DPP) ash acute toxicity estimation was done by exposing Cladoceran Pleuroxus hamulatus Birge, 1910 to different ash concentrations. Thus, this study was regarded as pioneering by evaluating these effluents’ harmful effects on the chosen laboratory food chain individuals. The LC50 of ash on P. hamulatus were 0.04, 0.02 and 0.01 ppt during 24, 48 and 72 hr. respectively. On the other hand, our result showed that the increase in the ash concentrations leads to the maximum increase in mortality percentages value. Additionally, there were some clear behavioral changes seen in the animals, including slowness at first, followed by settling on the bottom of the beakers with stopped thorax, antennae appendages and a weak heartbeat. It was also observed that the survival was inhibited, and the mortality rate increased which may be due to the presence of toxic ash elements and the pH level change, both of which had a negative impact. The current study concluded that the acute toxicity exposure on P. hamulatus had harmful effects on all biological aspects of this aquatic food chain organisms.